Photoinitiating Monomers Based on Diacrylamides - Karasu, Feyza; Dworak, Claudia; Kopeinig, Stefan; Hummer, Erwin; Arsu, Nergis; Liska, Robert (AMER CHEMICAL SOC, 2008)
Novel monomers with reactive diacrylamide units were developed as alternatives to common acrylate- or acryl amide-based functional groups. By using photo differential scanning calorimetry and ATR-IR spectroscopy, we were able to determine their theoretical polymerization heats and photopolymerization properties. Surprisingly, these new monomers exhibited high polymerization reactivity due to cyclopolymerization and showed self-initiating behavior under irradiation with UV light. As absorption of these photoinitiating monomers tails out at 320 nm, sensitizers were successfully employed to expand the spectral range of sensitivity.
Keywords: CYCLOPOLYMERIZATION; COPOLYMERIZATION; ALKYLATION; MECHANISM; Polymer Science